The Impact Of Greenpeance Anti-Palm Oil Campaign Towards Indonesian Palm Oil Export To Europe In 2008-2010 - Dini Tiara Sasmi (Journal of Diplomacy and International Studies, 2018)
This research explain about impact of Greenpeace anti palm oil campaign towards Indonesian palm oil export to Europe within year 2008 to 2010. At this time Indonesia are the biggest producer of palm oil country. Indonesia palm oil export has shown a lot of benefit to Indonesia economic growth. Palm oil itself has already beated other vegetable oil such as sunflower oil, rapeseed oil and soybean oil that originated comes from sub tropic area like Europe. Greenpeace anti palm oil campaign in Indonesia broughts many lost and disadvantages for Indonesia economy since many multi national coorporate decide to stop buy palm oil from Indonesia. This research used Qualitative analysis. Theory used in this research is GOs are used by nations theory by McCormick and Kihl (1979). The writer used data which was collected from books, encyclopedia, journal, and website to analyze the research. Finally, this research finds out how impacts of Greenpeace campaign towards Indonesia export to Europe in 2008-2010. The research also show a lot of evidences of falsehood of Greenpeace in using data to blame Indonesian Palm Oil Industry.